Analytical investigation of a boundary value problem for functional differential inclusion - Al-Issa, Sh.M.; Kaddoura, I.H.; Hamzae, H.M. (Carpathian Mathematical Publications, 2025)
This paper investigates the existence of mild solutions for an initial value problem involving fractional-order differential inclusions with nonlocal boundary conditions, specifically infinite-point or Riemann-Stieltjes integral conditions. We establish sufficient conditions for the uniqueness of the solution and examine its continuous dependence on the given data. To demonstrate the practical applicability of our findings, we conclude with two illustrative examples.